Melatonin and Nicotinamide Mononucleotide Attenuate Myocardial Ischemia/Reperfusion Injury via Modulation of Mitochondrial Function and Hemodynamic Parameters in Aged Rats. (May 2020) - Hosseini, Leila; Vafaee, Manouchehr S.; Badalzadeh, Reza
Ischemic heart diseases are the major reasons for disability and mortality in elderly individuals. In this study, we tried to examine the combined effects of nicotinamide mononucleotide (NMN) preconditioning and melatonin postconditioning on cardioprotection and mitochondrial function in ischemia/reperfusion (I/R) injury of aged male rats. Sixty aged Wistar rats were randomly allocated to 5 groups, including sham, control, NMN-receiving, melatonin-receiving, and combined therapy (NMN+melatonin). Isolated hearts were mounted on Langendorff apparatus and then underwent 30-minue ligation of left anterior descending coronary artery to induce regional ischemic insult, followed by 60 minutes of reperfusion. Nicotinamide mononucleotide (100 mg/kg/d intraperitoneally) was administered for every other day for 28 days before I/R. Melatonin added to perfusion solution, 5 minutes prior to the reperfusion up to 15 minutes early reperfusion. Myocardial hemodynamic and infarct size (IS) were measured, and the left ventricles samples were obtained to evaluate cardiac mitochondrial function and oxidative stress markers. Melatonin postconditioning and NMN had significant cardioprotective effects in aged rats; they could improve hemodynamic parameters and reduce IS and lactate dehydrogenase release compared to those of control group. Moreover, pretreatment with NMN increased the cardioprotection by melatonin. All treatments reduced oxidative stress and mitochondrial reactive oxygen species (ROS) levels and improved mitochondrial membrane potential and restored NAD + /NADH ratio. The effects of combined therapy on reduction of mitochondrial ROS and oxidative status and improvement of mitochondrial membrane potential were greater than those of alone treatments. Combination of melatonin and NMN can be a promising strategy to attenuate myocardial I/R damages in aged hearts. Restoration of mitochondrial function may substantially contribute to this cardioprotection.